2020
DOI: 10.1002/bjs5.50264
|View full text |Cite
|
Sign up to set email alerts
|

Impact of postoperative complications on survival after oesophagectomy for oesophageal cancer

Abstract: Background: Recent evidence suggests that complications after oesophagectomy may decrease shortand long-term survival of patients with oesophageal cancer. This study aimed to analyse the impact of complications on survival in a Western cohort. Methods: Complications after oesophagectomy were recorded for all patients operated on between January 2006 and February 2017, with severity defined using the Clavien-Dindo classification. Associations between complications and overall and recurrence-free survival were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
1
21
1
Order By: Relevance
“…Although short-term morbidity was increased after transhiatal minimally invasive esoph-agectomy, postoperative morbidity was comparable after transtho-racic minimally invasive and open esophagectomies in the present study. As a complicated postoperative course was associated with worse long-term outcomes, 10,15,20 prevention of short-term morbidity after minimally invasive esophagectomy should have an important focus.…”
Section: Discussionmentioning
confidence: 99%
“…Although short-term morbidity was increased after transhiatal minimally invasive esoph-agectomy, postoperative morbidity was comparable after transtho-racic minimally invasive and open esophagectomies in the present study. As a complicated postoperative course was associated with worse long-term outcomes, 10,15,20 prevention of short-term morbidity after minimally invasive esophagectomy should have an important focus.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, it has been shown that early detection of PIC is essential not only for the treatment of complications but also for patient survival [ 20 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ]. PICs, according to the definition used for this paper, include surgical site infections, pneumonia, pleural empyema, leakage or necrosis of the gastric conduit, and anastomotic leakage [ 33 , 39 ]. Indisputably, these complications are of different importance and severity.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative complications are independently associated with decreased survival due to cancer recurrence [ 30 ], and prevention of complications may improve survival [ 31 ]. Wang W et al reported that thoracic epidural anesthesia did not affect the risk of AL occurrence after esophageal surgery for cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%